Socioeconomic profile and preferences of tilapia consumers at te lower Sao Francisco river, Alagoas-Brazil - Araujo, Daniel de Magalhaes [UNESP]; Cardoso, Alyson do Nascimento; Calazans, Eline Monteiro (Sindicato Secretarias Estado Sao Paulo, 2023)
Were interviewed 104 and 105 consumers at Penedo (PEN) and Porto Real do Colegio (PRC) street markets - Alagoas, Brazil. When citing tilapia as a preferred species for consumption (26 and 22 consumers), they were interviewed for socioeconomic characterization, and to diagnose fish acquisition and consumption preferences. There were a majority of men in PEN and women in PRC, the mean age being 41.77 and 44.62 years. Lows schooling and family income are common characteristics. In PEN, the preferred and most consumed meats are fish (42.31% and 38.46%), while in PRC beef is preferred (52.38%), but also bovine and fish (36.36%). Fish were considered the second preferred meat option and most consumed by 42.85 and 41.17% of respondents in PEN and 36.84% and 27.77% in PRC. For these consumers, who declared tilapia as their preferred specie, the other preferred species were continental fishes: tambaqui and curimata-pacu (42.11 and 26.32% in PEN, 50.00 and 25.00% in PRC). Most consumers prefer to buy live tilapias, consider R$ 6.50 the fair value per kilogram and give up the purchase if the value exceeds R$ 10,00. The clear majority of respondents consider the quality of tilapia marketed in municipalities good or great.
Keywords: Colossoma macropomum; Fish Consumer; Preference of fish Consume; Oreochromis niloticus; Productive Fish Chain